Peran Mahasiswa KKN dalam Penguatan Pendidikan Keagamaan Anak melalui Peringatan Isra’ Mi’raj dan Pawai Obor di Jorong Gando Nagari Paninggahan - Al-Ikhlas; Mawar Damara; Farlingga Fadjrin; Rahmad Al-Anshori; Raihani Syaidah; Randes Dwi Saputra (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Religious education serves as a fundamental pillar in shaping children's character amidst the challenges of the digital era. Students participating in the Community Service Program (Kuliah Kerja Nyata - KKN) hold a strategic role as facilitators of religious value transformation within the community. This article aims to analyze the contribution of KKN students in strengthening children's religious education in Nagari Paninggahan through the integration of the Isra' Mi'raj commemoration and the torch parade tradition (pawai obor). The research methodology employs a descriptive qualitative approach with the Participatory Action Research (PAR) model. The findings indicate that the active involvement of the community in religious lectures and the torch parade successfully enhanced children's spiritual understanding, strengthened social solidarity, and preserved local cultural heritage as an effective medium for Islamic proselytization (dakwah).